ANALISIS FRAUD DIAMOND DALAM MENDETEKSI FRAUDULENT FINANCIAL STATEMENT - Mahira Firnanda; Hotman Tohir Pohan (STMIK Widuri Jakarta, 2023)
This study aims to analyze fraud diamonds in detecting fraudulent financial statements. This research was conducted using quantitative methods. In this study, the population was taken from banking companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. The type of data used in this study is secondary data, where this data comes from the company's financial statements. This study also used a purposive sampling method in selecting the sample and produced 41 banking companies over a period of 3 years with a total of 123 observed data samples. The analysis technique used by the authors in this research is the classical assumption test, and multiple linear regression tests. The test results in this study show that Financial Stability and Directors Change had no effect on Fraudulent Financial Statements, External Pressure and Ineffective Monitoring had negative effect on Fraudulent Financial Statements. Meanwhile, Financial Targets had a positive effect on Fraudulent Financial Statements.